Problems of Islamic Law Compilation In Indonesia - Arip Purkon (SALAM: Jurnal Sosial dan Budaya Syar-i, 2018)
Abstract.Islamic Law Compilation is one of the efforts to implement Islamic law in Indonesia constitutionally. Islamic Law Compilation covers three legal fields, namely marriage, inheritance and benefiction. The Islamic Law Compilation contributes positively in providing legal certainty, especially for judges in religious courts. In addition, there are still a number of problems related to the Islamic Law Compilation, namely the issue of socialization, equality of perception and the fear of reducing Islamic law.Keywords: Islamic Law Compilation, Marriage Law, Inheritance Law, Benefaction   Abstrak.Kompilasi Hukum Islam merupakan salah satu upaya untuk mengimplementasikan hukum Islam di Indonesia secara konstitusional. Kompilasi Hukum Islam mencakup tiga bidang hukum, yaitu perkawinan, waris dan wakaf. Kompilasi Hukum Islam memberikan kontribusi yang positif dalam memberikan kepastian hukum, khususnya untuk para hakim di pengadilan agama. Selain itu, masih ada beberapa masalah terkait Kompilasi Hukum Islam, yaitu masalah sosialisasi, persamaan persepsi dan adanya kekhawatiran tereduksinya hukum Islam.Kata Kunci: Kompilasi Hukum Islam, Hukum Perkawinan, Hukum Waris, Wakaf